Infantile Hypertrophic Pyloric Stenosis Analysis of 84 Cases (TAJ: Journal of Teachers Association, 2009)
This is a descriptive study carried out in the Department of Pediatric Surgery, Rajshahi Medical College Hospital and in the private clinics of Rajshahi, during the period of November 2000 to October 2004. Total 84 patients were treated by Ramstedt's pyloromyotomy after proper resuscitation. The male to female ratio was 5:1. Most of the patients presented to us within 40 days of age (90%). In 90% cases diagnosis were done on clinical basis. The diagnosis is confirmed by barium meal x-ray in 60 cases and sonogram in 71 cases. Serum electrolytes were estimated in all patients. There was metabolic derangement in more than 80% cases. There was no postoperative mortality. Oral feeding started after 6 hours postoperatively in 81 cases. Inadvertent mucosal perforation occurred in 3 cases and that was recognized and repaired successfully without any ill effect. Superficial wound infection encountered in 8.33% cases. doi: 10.3329/taj.v18i1.3297 TAJ 2005; 18(1): 14-16